IDENTIFIKASI KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPA DI SDN GUGUS 1 KECAMATAN DUREN SAWIT - Tri Wahyuni, Ida; Sari, Prima Mutia; Kowiyah , Kowiyah (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
Abstrack: This study aims to determine the identification of students’ critical thinking skills in science learning at SDN Gugus 1 Duren Sawit District. This study used a quantitative descriptive research method using survey method. The research population was SDN Gugus 1 Duren Sawit District and the sample was SDN Duren Sawit 02, 10 and 14 Pagi. The sampling technique was cluster random sampling. The data was collected by using critical thinking skills tests, interviews and documentation. The results showed that the average of critical thinking skills in SDN Gugus 1 students Duren Sawit District was 35,14 in the moderate category. The average score of critical thinking in SDN Duren Sawit 02 Pagi was 39,74 in the moderate category, SDN Duren Sawit 10 Pagi was 34,91 in the low category, and SDN Duren Sawit 14 Pagi was 30,78 in the low category. The highest furthemore indicator of critical thinking in SDN Gugus 1 Duren Sawit District, namely SDN Duren Sawit 02 Pagi the average score was 39, 74 in the moderate category, SDN Duren Sawit 10 Pagi got an average score of 34,91 with the low category and SDN Duren Sawit 14 Pagi have an average value of 30,78 in the low category, while the results of the study on the average of each indicator show that the highest indicator in SDN Gugus 1 Duren Sawit District on the indicator provides further explanation with an average score 38 and the lowest indicator in SDN Gugus 1 Duren Sawit District on indicators og managing strategies and tactics with an average score of 31.